Demographic Dividends for India: Evidence and Implications Based on National Transfer Accounts - Laishram Ladusingh; M. R. Narayana (Asian Development Bank (ADB), 2011)
There is a lack of verifiable evidence on the period and magnitude of the demographic dividends in India, a gap policy makers must address when setting priorities for human resource and capital investment to harvest the economic benefits of the demographic transition currently under way. This study attempts to fill this gap by quantifying the demographic dividends using National Transfer Accounts framework and by indicating their implications for equity. Our analysis projects that income per effective consumer could increase by 24.9% from 2005 to 2035 - 9.1% from the first demographic dividend and 15.8% from the second demographic dividend - and that the second dividend will be stable up to 2070. However, unless appropriate institutional reforms create an environment conducive to accumulating assets and raising productivity, India will find it difficult to meet the fiscal challenges posed by population aging.
hdl:11540/1988
Keywords: 330; Bevölkerungsentwicklung; Wirtschaftswachstum; Öffentliche Sozialleistungen; Indien